Distingsi Studi Hadis di PTKIN UIN Raden Fatah Palembang - Adriansyah NZ; Beko Hendro (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2020)
Along with the change in nomenclature regarding the Naming of Islamic Religious Colleges, Faculties, Departments at Islamic Universities in the Decree of the Minister of Religion Number 36 of 2009, then the Decree of the Minister of Religion was strengthened by the Decree of the Director General of Islamic Education Number 3389 of 2013 where the scientific study of Hadith made into two study programs, namely the Science of the Koran and Tafsir (IAT / IQT) and the Science of Hadith (ILHA). In further developments, the study of hadith at the State Islamic Religious College (PTKIN) Indonesia has a pattern, variety and characteristics according to their respective peculiarities. The various types and forms of courses offered in hadith studies indicate a continuous dynamic. After conducting a study and discussion of the distinction of hadith studies in the Hadith Science Study Program curriculum of Raden Fatah State Islamic University Palembang and its relevance to the Distinction of Higher Education at Raden Fatah State Islamic University Palembang, the authors conclude that there is a relationship and connection between the distinction of UIN Raden Fatah Palembang and the study. hadith contained in the Hadith Science Study Program curriculum, namely the Malay Islamic Civilization Distingsi. This relevance is evidenced by at least four courses contained in the Hadith Science Study Program curriculum that support the Higher Education Distinction of Raden Fatah State Islamic University, Palembang. The four courses are; 1) Malay Islamic Studies, 2) Tahfiz Hadith Arbain Imam al-Tarmasi, 3) Study of the Archipelago Hadith and 4) Living Hadith. Judging from the hadith study map, there are three domains of hadith study, namely ulumul hadith (theoretical), hadith (understanding) and the study of hadith characters / books. The four subjects mentioned above describe the scope of all hadith studies connected to the distinction of the Raden Fatah State Islamic University of Palembang, namely Malay Islamic Civilization. In another part, some of the researches of Hadith Science Study Program lecturers also strengthen the existence of the distinction of Malay Islamic Civilization contained in the works of Hadith Science Study Program lecturers.